Early-time Millimeter Observations of the Nearby Type II SN 2024ggi - Maokai Hu; Yiping Ao; Yi Yang; Lei Hu; Fulin Li; Lifan Wang; Xiaofeng Wang (The Astrophysical Journal Letters)
The short-lived ionized emission lines in early spectroscopy of the nearby Type II supernova SN 2024ggi signify the presence of dense circumstellar matter (CSM) close to its progenitor star. We proposed the Atacama Large Millimeter/submillimeter Array (ALMA) observations by its Director's Discretionary Time program to catch the potential synchrotron radiation associated with the ejecta–CSM interaction. Multiepoch observations were conducted using ALMA band 6 at +8, +13, and +17 days after the discovery. The data show nondetections at the position of SN 2024ggi with a 3 σ upper limit of less than 0.15 mJy, corresponding to a luminosity of approximately 8 × 10 ^24 erg s ^−1 Hz ^−1 . In this paper, we leverage the nondetections to place constraints on the properties of CSM surrounding SN 2024ggi. We investigate both the Wind and Eruptive models for the radial distribution of CSM, assuming a constant mass-loss rate in the Wind model and a distance-variant mass-loss rate in the Eruptive model. The derived CSM distribution for the Wind model does not align with the early-time spectral features, while the ALMA observations suggest a mass-loss rate of ~5 × 10 ^−3 M _⊙ yr ^−1 for the Eruptive model. Conducting multiepoch millimeter/submillimeter observations shortly after the explosion, with a cadence of a few days, could offer a promising opportunity to capture the observable signature of the Eruptive model.